2018
DOI: 10.1590/1678-4162-9209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Coagulase-Negative Staphylococci and pheno-genotypic beta lactam resistance evaluation in samples from bovine Intramammary infection

Abstract: This study aimed to identify Coagulase-Negative Staphylococci (CoNS) species isolated from bovine mastitis, through phenotypic and PCR-RFLP (Restriction Fragment Length Polymorphism-Polimerase Chain Reaction) methods and to compare both techniques to matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) technique. Among them, the PCR-RFLP method, using a partially conserved sequence of the groEL gene, is a promising alternative, because of its reproducibility and reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Despite the phenotypic resistance observed in S. gallinarum strains, none of resistance genes (mecA genes and blaZ) tested in this study was detected in this species. These findings corroborated with Melo et al (2018), that observed the same pattern evaluating β-lactam resistance in CoNS isolates from bovine intramammary infection. These results could support the hypothesis that these isolates have higher degrees of variability or suffer mutations that prevent its detection requiring further studies to better understanding.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the phenotypic resistance observed in S. gallinarum strains, none of resistance genes (mecA genes and blaZ) tested in this study was detected in this species. These findings corroborated with Melo et al (2018), that observed the same pattern evaluating β-lactam resistance in CoNS isolates from bovine intramammary infection. These results could support the hypothesis that these isolates have higher degrees of variability or suffer mutations that prevent its detection requiring further studies to better understanding.…”
Section: Discussionsupporting
confidence: 90%
“…In animals, S. aureus and CoNS have been reported to cause mastitis, septicemia and arthritis in poultry (Simojoki et al, 2011;Sampimon et al, 2011). CoNS are increasingly being recognized as an important cause of mastitis in cattle in Kenya, Tanzania, Egypt, Tunisia, Czech Republic and other parts of the world including Europe, South America and the Middle East (Mbindyo et al, 2020;Soares et al, 2012;El-Razik et al, 2017;Srednik et al, 2017;Pyatov et al, 2017 andMelo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results presented in this study are in addition to others performed in the country that have identified cases of bovine mastitis due to MRSA and MRS . It should serve as a warning to animal health authorities regarding the improvement of programs for the control and rational use of antimicrobials in veterinary medicine (SOARES et al, 2012;MATOS, 2014;SILVA et al, 2014b;SANTOS et al, 2016;MELO et al, 2018). High use of antimicrobials or their indiscriminate use contributes to the selection and persistence of MRS strains; and consequently, their spread throughout the agricultural environment.…”
Section: Molecular Identification Of ---------Staphylococcus Spp 3 --------Molecular Identification Of Methicillinmentioning
confidence: 99%
“…Contact between humans and animals positive for MRS and vice versa, may also favor pathogen transmission between species, and the environment may be a source of infection for both (JUHÁSZ-KASZANYITZKY et al, 2007). In Brazil, few studies have identified cases of mastitis caused by MRS (SOARES et al, 2012;MATOS, 2014;SANTOS et al, 2016;MELO et al, 2018). However, no study conducted in the country has evaluated and detected the presence of MRS isolates in cases of mastitis, workers, and the milking environment, and a possible genetic correlation between MRS isolates from various sources in the agricultural environment.…”
Section: Introductionmentioning
confidence: 99%